A Decision Support System for the Selection of Social Assistance Recipients: Comparison of SAW and TOPSIS Methods in Ponggol Village - Meidika Arni Saraswati; Shevti Arbekti Arman; Fahrul Razi (Jurnal Teknologi Informasi (JUTECH), 2025)
The selection process for prospective recipients of the Program Keluarga Harapan (PKH) social assistance in RW. 03, Ponggol Village, is currently conducted manually, which is time-consuming and prone to subjectivity. To address these issues, this research aims to develop a web-based decision support system (DSS). The system was designed using PHP and MySQL for the backend, along with HTML, CSS, and JavaScript for the frontend. Two DSS methods, namely Simple Additive Weighting (SAW) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), were implemented to perform calculations and rank alternatives based on five criteria determined through an interview. System testing results show that both the SAW and TOPSIS methods successfully provided consistent ranking results for ranks 1 to 5. Therefore, the developed system can serve as an objective, transparent, and efficient tool for decision-makers in determining the most deserving recipients of social assistance.